2007
DOI: 10.1007/978-3-540-74853-3_11
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Location Error Estimation

Abstract: Abstract. Many existing localization systems generate location predictions, but fail to report how accurate the predictions are. This paper explores the effect of revealing the error of location predictions to the end-user in a location finding field study. We report findings obtained under four different error visualization conditions and show significant benefit in revealing the error of location predictions to the user in location finding tasks. We report the observed influences of error on participants' st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 19 publications
0
61
0
Order By: Relevance
“…Similarly, Rukzio et al found that displaying uncertainty slowed down user performance, because users would double-check fields with lower certainty [19]. In studies of presenting location information, visualizations of location certainty were found to improve user performance with location-based services [6,13]. Though not explicitly investigating about uncertainty, Yan et al found that displaying higher trust and reputation values of mobile applications increased users' willingness to continue using them [22].…”
Section: Displaying Uncertainty In Context-aware Applicationsmentioning
confidence: 99%
“…Similarly, Rukzio et al found that displaying uncertainty slowed down user performance, because users would double-check fields with lower certainty [19]. In studies of presenting location information, visualizations of location certainty were found to improve user performance with location-based services [6,13]. Though not explicitly investigating about uncertainty, Yan et al found that displaying higher trust and reputation values of mobile applications increased users' willingness to continue using them [22].…”
Section: Displaying Uncertainty In Context-aware Applicationsmentioning
confidence: 99%
“…In each task, the uncertainty was visualised according to either the referred basic technique, which previously proved to be beneficial for navigation tasks (Dearman et al 2007), or the experimental design under investigation. The results of the study show that the extended design turns out to be at least as good to use as the basic one, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…But some factors about uncertainty can only become known when they appear, so that they need to be processed and visualised at run-time using the information at hand. For example, Dearman et al (2007) visualisation showing the predicted position only, a circle centred in the predicted position and extending proportionally to the speed of walking, and street segments, i.e. the routes along which the participants could actually walk, coloured also according to the walking speed.…”
Section: Visualising Uncertainty About Locationmentioning
confidence: 99%
“…As a study by Dearman et al [18] has shown, even this unspecific knowledge of the error distribution helps users of an LBS to perform better when e.g., solving location-specific tasks.…”
Section: A Error Distributionmentioning
confidence: 99%
“…The authors of [18] also introduced the use of multiple regression to estimate the position error. Using the training data and a smaller amount of test measurements for the reference spots, the system operator computes a linear model of the error that has to be expected based on a defined set of signal features.…”
Section: B Multiple Regressionmentioning
confidence: 99%